Regulation of Aqueous Humor Dynamics by Hydrogen Sulfide: Potential Role in Glaucoma Pharmacotherapy - Ohia, Sunny E. (J Ocul Pharmacol Ther, 2018)
Hydrogen sulfide (H(2)S) is a gaseous transmitter with well-known biological actions in a wide variety of tissues and organs. The potential involvement of this gas in physiological and pathological processes in the eye has led to several in vitro, ex vivo, and in vivo studies to understand its pharmacological role in some mammalian species. Evidence from literature demonstrates that 4 enzymes responsible for the biosynthesis of this gas (cystathionine β-synthase, CBS; cystathionine γ-lyase, CSE; 3-mercaptopyruvate sulfurtransferase, 3MST; and d-amino acid oxidase) are present in the cornea, iris, ciliary body, lens, and retina. Studies of the pharmacological actions of H(2)S (using several compounds as fast- and slow-releasing gas donors) on anterior uveal tissues reveal an effect on sympathetic neurotransmission and the ability of the gas to relax precontracted iris and ocular vascular smooth muscles, responses that were blocked by inhibitors of CSE, CBS, and K(ATP) channels. In the retina, there is evidence that H(2)S can inhibit excitatory amino acid neurotransmission and can also protect this tissue from a wide variety of insults. Furthermore, exogenous application of H(2)S-releasing compounds was reported to increase aqueous humor outflow facility in an ex vivo model of the porcine ocular anterior segment and lowered intraocular pressure (IOP) in both normotensive and glaucomatous rabbits. Taken together, the finding that H(2)S-releasing compounds can lower IOP and can serve a neuroprotective role in the retina suggests that H(2)S prodrugs could be used as tools or therapeutic agents in diseases such as glaucoma.